Support Systems in International Teaching Practice Programs: Experiences of Students from a Private University - Ardini, Anandayu Suri; Prasetya, Willy; Murtafi’ah, Banatul (KnE Social Sciences, 2025)
In international teaching practice (ITP), support systems are vital in helping students navigate cultural differences and overcome various challenges while ensuring they meet their professional responsibilities. Although the number of Indonesian university students participating in ITP is on the rise, there is limited research on how support systems from sending institutions are provided. This paper aims to document and describe the strategies employed by a study program at a private university that has extensive experience sending students abroad for teaching practice. This paper examines the role of support systems and seeks to raise awareness about their importance for students in ITP. In 2023, 16 participants and in 2024, 9 participants were involved in the program, providing them with immersive teaching experiences in different cultural and educational environments. Data were gathered through Focus Group Discussions (FGDs) with all participants, focusing on their challenges, strategies, and skills gained. The findings highlight the crucial role of a strong support system in enhancing participants’ adaptability and professional growth during international teaching experiences. This paper contributes valuable insights into the necessity of comprehensive support systems for students undertaking international teaching practice, emphasizing the importance of structured assistance from sending institutions.